A framework for understanding the quality of evidence use in education. Issue 2 (3rd April 2022) - Rickinson, Mark; Cirkony, Connie; Walsh, Lucas; Gleeson, Joanne; Cutler, Blake; Salisbury, Mandy
ABSTRACT: Background: There are growing expectations internationally that schools and systems will use research evidence to inform their improvement efforts. Such developments raise important questions about what it means to use research evidence well in education. Purpose: To date, there has been wide-ranging debate about what counts as quality evidence, but very little dialogue about what counts as quality use . In response, this article presents a conceptual framework to define and elaborate what quality use of research evidence might mean in relation to education. Method: The framework is informed by a cross-sector systematic review and narrative synthesis of 112 relevant publications from four sectors: health, social care, education and policy. The review explored if, and how, quality of evidence use had been defined and described within each of these sectors in order to inform a quality use framework for education. Findings: Based on the cross-sector review, quality use of research evidence is framed in terms of two core components: (1) appropriate research evidence and (2) thoughtful engagement and implementation, supported by three individual enabling components (skillsets, mindsets and relationships) and three organisational enabling components (leadership, culture and infrastructure), as well as system-level influences. Conclusions: There is potential for this framework to inform current approaches to the use of research in education. There is also an important need to test and refine its components through further empirical investigation, theoretical inquiry and intervention development.